Game theoretic packet relaying model for wireless ad hoc networks. (22nd June 2009) - Yan, Lu
In wireless ad hoc networks, nodes are both routers and terminals, and they have to cooperate to communicate. Cooperation at the network layer means routing (finding a path for a packet) and forwarding (relaying packets for others). However, because wireless nodes are usually constrained by limited power and computational resources, a selfish node may be unwilling to spend its resources in forwarding packets that are not of its direct interest, even though it expects other nodes to forward its packets to the destination. In this paper, we propose a game theoretic model to facilitate the study of the non cooperative behaviours in wireless ad hoc networks and analyse incentive schemes to motivate cooperation among wireless ad hoc network nodes to achieve a mutually beneficial networking result.